The Impact of Catholic Culture on the Cultural and Spiritual Lives of Contemporary Vietnamese Students - Anh, Đỗ Thị Ngọc; Cường, Nguyễn Anh (Journal of Ecohumanism, 2024)
Catholicism has been practiced in Vietnam for more than four centuries. Over seven and a half million people are members of the Vietnamese Catholic community as of the year 2022. The most notable examples of Catholic culture in Vietnam are these forms. A deeper relationship between Vietnamese spirituality and Catholic culture has been established due to the phenomenon known as "Vietnamese" Catholicism. Beyond the confines of the Christian community, Catholic culture is now pervasive throughout Vietnamese society. Students constitute a significant component of the Vietnamese population, particularly the younger generation. In light of this, the question arises as to how the spirituality of Vietnamese students has been influenced by Catholic culture. In order to investigate the process of Catholic cultural assimilation among Vietnamese people, the writers use empirical analysis to investigate four typical narratives: New Year's Day on January 1, Valentine's Day on February 14, and Christmas Day on December 25. It provides a complete explanation of the cultural shifts in society due to globalization. In addition to being inspired by Confucian culture, Vietnam is open to Western culture, particularly Catholicism. Vietnam has a long and illustrious past and a unique culture.